2005
DOI: 10.1074/jbc.m412433200
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of cGMP-dependent Protein Kinase Type I during Medaka Fish Embryogenesis

Abstract: We isolated and characterized cDNA clones (PKG I␣ and PKG I␤) for medaka fish cGMP-dependent protein kinase (PKG) I␣ and I␤, and demonstrated that both are expressed in the embryos after late gastrula stage. Whole-mount in situ hybridization using each isoformspecific probe revealed that the transcripts of the PKG I␣ gene were present in the spinal cord and gill arch, whereas those of the PKG I␤ gene were only weakly expressed in these organs, but highly expressed in the otic vesicles. Injection of PKG I␣-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…On the other hand, for may also affect developmental processes that facilitate visual pattern memory to a certain extent. This is not surprising, though, as PKG has been shown to be involved in the development of the nervous system in Drosophila and other species (Renger et al 1999;Yamamoto and Suzuki 2005;Zhang et al 2005).…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, for may also affect developmental processes that facilitate visual pattern memory to a certain extent. This is not surprising, though, as PKG has been shown to be involved in the development of the nervous system in Drosophila and other species (Renger et al 1999;Yamamoto and Suzuki 2005;Zhang et al 2005).…”
Section: Discussionmentioning
confidence: 96%
“…In this regard, it is of note that cGMP activates Shh signaling in mammals (38). Given that protein kinase G (PKG) activated by cGMP phosphorylates Gli3, resulting in activation of Shh signaling (39), it is possible that the FKBP38-ANKMY2 axis controls Shh signaling via the cGMP-PKG pathway.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated that an increase of intracellular cGMP concentration enhances the Shh response (13,14). At least two distinct classes of guanylyl cyclases (GCs), which catalyze the conversion of GTP into cGMP, can be activated in response to extracellular cues.…”
Section: Introductionmentioning
confidence: 99%
“…Six of these sites are present in the sequence of Ci, and several are conserved in Gli1 and Gli2. In NO-sensitive neuroblastoma cells, Gli3 is phosphorylated after treatment of 8-bromo-cGMP (14). Because Gli3 is also phosphorylated by PKA, PKG could enhance Shh signaling either by phosphorylating Gli3 at distinct sites or by interfering with phosphorylation of Gli3 by PKA.…”
mentioning
confidence: 97%
See 1 more Smart Citation